2021
DOI: 10.1002/csc2.20515
|View full text |Cite
|
Sign up to set email alerts
|

Daily light integral requirements for bermudagrass and zoysiagrass cultivars: Effects of season and trinexapac‐ethyl

Abstract: Shade is a major problem facing turf managers worldwide. Availability of low-cost devices and methods for quantifying daily light integral (DLI) offer the turf manager the ability to more precisely determine DLI levels in shade, yet minimal DLI requirements for acceptable turf quality (DLI m ) for many commonly used warm-season turf cultivars grown under longer-term chronic shade stress have not been extensively tested. The objectives of this 2-yr field shade study were to (a) determine effects of growth regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…In heavy (70% and 90%) shade, TQ generally declined from July to October for both cultivars, likely due to the increasing duration of exposure to low‐light conditions. In general, more favorable turf performance has been reported for short‐term compared to long‐term (or permanent) shade conditions (Bunnell et al., 2005; Chen et al., 2021; Chhetri et al., 2019; Zhang et al., 2017). Although shading lasted 4 months per year in this study, PV performed well in both 70% and 90% shade levels in this study, whereas CONV KBG TQ ranged from 4.0 to 6.6 under 90% shade, PV maintained quality of 6.0–7.9 under these shade levels.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In heavy (70% and 90%) shade, TQ generally declined from July to October for both cultivars, likely due to the increasing duration of exposure to low‐light conditions. In general, more favorable turf performance has been reported for short‐term compared to long‐term (or permanent) shade conditions (Bunnell et al., 2005; Chen et al., 2021; Chhetri et al., 2019; Zhang et al., 2017). Although shading lasted 4 months per year in this study, PV performed well in both 70% and 90% shade levels in this study, whereas CONV KBG TQ ranged from 4.0 to 6.6 under 90% shade, PV maintained quality of 6.0–7.9 under these shade levels.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, previous research has shown application of trinexapac‐ethyl (a GA inhibitor) resulted in increased leaf chlorophyll contents of NuStar KBG (Ervin & Koski, 2001). While GA2ox transformation effects on shade tolerance of turfgrasses have been limited to a single creeping bentgrass study (Studzinska et al., 2012), trinexapac‐ethyl application has shown significant improvement in shade tolerance of both cool‐season and warm‐season turfgrasses (Chen et al., 2021; Qian et al., 1998; Steinke & Stier, 2003a, 2003b; Stier & Rogers, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations